ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN DAYA SAING UMKM SIOMAY DAN BATAGOR DI STADION MAULANA YUSUF - Rifai, Nadilah; Hafidoh, Miftah Komala Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the marketing strategies applied by siomay and batagor MSME players in the Maulana Yusuf Stadium area, Serang City, and evaluate their contribution to increasing business competitiveness. The method used is descriptive qualitative with data collection techniques through in-depth interviews with business actors. The results showed that the marketing strategy is still conventional, relying on strategic location, taste quality, friendly service, and cleanliness. Although they have not utilized digital media, business owners have a good practical understanding of business management. This study concludes that these simple strategies are quite effective in retaining customers, but not optimal for market expansion. Therefore, assistance and training in modern marketing are urgently needed so that MSMEs can sustainably improve competitiveness amidst the growing market challenges.